Padre Jesuíno do Monte Carmelo: a construção barroca da Urbe Colonial (São Paulo 1774–1819) - Oliveira, Francisco Isaac Dantas de (2023)
Baroque was an artistic, cultural, political, and religious style. It has started in Modern Europe and has found fertile ground in America. On this continent it proved to be important in the cultural process to educate the Indians and, by extension, westernized the natives. Baroque built and helped life in São Paulo city to be defined during the second half of the 18th century. Several governments of the Captaincy of São Paulo used art in the social construction of its capital city. The State and the Catholic Church were largely responsible for the creation of new civil and sacred spaces within urban boundaries. There are several documents reporting the success in educational and westernizing projects in São Paulo city, some letters establish new towns and villages in the hinterlands of São Paulo, the purpose was to serve the Indians with religious instruction and catechesis; such documents, therefore, make explicit the government's intention to “civilize” people who traditionally had occupied that region. From these documents we can realize the “civilizing” project the São Paulo colonial government carried out with indigenous people. A political and social project that sought to westernize indigenous people through art and images. In such context, I aim at figuring out how artist and priest Jesuíno do M. Carmelo participate in the construction of this baroque city. Him was extensively studied by historian Mário de Andrade in a period when he tried to understand the historical construction of Baroque through its remaining patrimony in the city and state of São Paulo. He ended up going further, building a national identity thanks to discussions on the concept of patrimony, a hot topic by the 1930s in the old SPHAN. Father Jesuíno was a mestizo man, probably born in 1764 in the city of Santos, on São Paulo coast. He circulated through the hinterland of the captaincy, through cities such as Itu and São Paulo. He produced paintings, musical scores, altars, and architectural projects for religious Orders in the capital; and public works financed by individuals and the Catholic Church. Jesuíno traveled through several cities and his biography deserves another contemporary look. And this is what I propose to do in this thesis. I repeatedly resorted to the research carried out by Mário de Andrade, a great enthusiast of the priest's work, and to images and documentation from national and foreign archives. I aim to understand the construction of the colonial city based on baroque art, the process of westernization imposed to indigenous people in the late eighteenth century in the captaincy of São Paulo, and Jesuíno's work within this baroque policy to elaborate the city. The methodology used in this research bases on examining 18th century ample documentation, more specifically Governors' Ofícios reporting aspects of local administration to their superiors in Lisbon. I carried out a deep analysis and a bibliographic review of what has already been studied on the subject, and I also did an iconographic study of Father Jesuíno's paints